Study on Student Satisfaction at Manado State University - Kimbal, Grace; Lumapow, Harol R.; Rawis, Joulanda A. M; Lengkong, Jeffry S. J. (JR Education, 2024)
Study This aim to: analyze, describe, and explain about influence of the performance of employees’ facilities, and infrastructure in a way direct to motivation work and satisfaction of students at Manado State University as well influence performance employees and facilities and infrastructure to satisfaction student via motivation Work. Method study that is: approach quantitative with analysis path (path analysis), subject study consisting of 133 people from 12th semester Class of 2017 students in 7 Faculties. Results study show that 1) Employee performance (X1) has an effect positive and significant to Satisfaction Student (Y) with calculated t value 2.749 > 1.979 and p-value (0.007) smaller than 0.05. 2) Facilities and Infrastructure (X2) have an influence positive and significant to Satisfaction Student (Y) with a calculated t-value of 3,349 > 1.979 and p-value more (0.001) small from 0.05. 3) Employee performance (X1) has an influence positive and significant to Motivation Work (Z) with a calculated t-value of 4.838 > 1.979 and p-value (0.000) smaller than 0.05. 4) Facilities and Infrastructure (X2) have an influence positive and significant to Motivation Work (Z) with a calculated t-value of 5.413 > 1.979 and a p-value (0.000) smaller than 0.05. 5) Motivation Work (Z) has an effect positive and significant to Satisfaction Student (Y) with a calculated t-value of 4.453 > 1.979, and a p-value more (0.000) small from 0.05. 6) Employee performance (X1) has an influential significance on student satisfaction (Y) through work motivation (Z), with a p-value of more than 0.001 small from 0.05. 7) Facilities and Infrastructure (X2) have an influence significant on student satisfaction (Y) through work motivation (Z), with a p-value of more than 0.001 small from 0.05. With thereby Can withdraw the conclusion namely Employee Performance (X1) and Facilities and Infrastructure (X2). direct influence to Motivation Work (Z) and Satisfaction Student (Y) at Manado State University. Employee Performance (X1) and Facilities and Infrastructure (X2). No direct influence on Satisfaction Student (Y) at Manado State University via Motivation Work (Z).